Dinamika Kebijakan Kepala Madrasah dalam Meningkatan Kompetensi Guru Pendidikan Agama Islam - Salistya Irfani; Saiful Hadi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Islamic Religious Education (PAI) teachers in madrasahs (Islamic schools) still face fundamental challenges in optimizing the quality of the learning process, including a lack of creativity in applying teaching methods and limited access to continuous professional development programs. In this context, the madrasah principal plays a crucial role in shaping institutional policy and fostering the capacity and competence of educators. This study aims to examine in depth the policy dynamics formulated and implemented by the madrasah principal to enhance the competence of PAI teachers at MTs Miftahul Ulum Pagendingan (Galis District, Pamekasan Regency), analyzing the dimensions of policy planning, implementation, and evaluation. Methodologically, the study adopts a case study approach within a qualitative research framework. Data collection involved three primary instruments field observation, in-depth interviews, and document analysis engaging the principal and PAI teachers responsible for subjects such as Islamic Cultural History (SKI), Fiqh (Islamic Jurisprudence), Al-Qur'an-Hadith, and Aqidah-Akhlaq (Islamic Creed and Ethics). Data analysis followed an interactive model comprising data reduction, data display, and systematic conclusion drawing. To ensure data validity, the study employed simultaneous source and method triangulation techniques. The findings indicate that the principal's policies were realized through several strategic programs, including structured academic supervision, active participation in Subject Teacher Forums (MGMP), capacity-building training, and the use of technology-based digital platforms such as Pintar Kemenag. The implementation of these policies has demonstrably contributed to strengthening the educators' pedagogical and professional competencies as well as their digital literacy, although practical obstacles remain that require more comprehensive attention.